An Analysis of Teachers' Capability in Implementing Online Learning During The Covid-19 Pandemic - Nur, Fauziah; Syaukani, Syaukani; Salminawati, Salminawati (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the ability of teachers to carry out online learning during the Covid-19 pandemic. The background of the research is at SD IT Khairul Imam Medan, conducted qualitatively with analytical descriptive method. Obtaining data used interview, observation, and documentation studies. Data analysis uses reduction, data display, and verification techniques. The data was declared valid after going through the triangulation technique test. The results of this study indicate that the teacher of SD IT Khairul Imam Medan is competent (capable) in carrying out online learning during the Covid pandemic. This is indicated by (1) the school's efforts to provide virtual workshops, training, and webinars on making lesson plans (RPP); and (2) training for teachers in the use of online applications as online learning media. Furthermore, some factors support the implementation of online learning at the school, namely the provision of free wifi facilities in schools and the use of free data packages from the government for the process of implementing online learning. Even so, there are also inhibiting factors, namely unstable network access (signal) constraints, online RPP Mode that is not in accordance with the reality of its implementation, and the lack of discipline and honesty of students in carrying out assignments.